Quantification of road user savings. - Weille, Jan de ([Washington, International Bank for Reconstruction and Development]; distributed by Johns Hopkins Press, 1966)
The paper tries to provide a better basis for estimates of the so-called road user savings resulting from road improvements
Includes bibliographical references
osc 07/03/2019
Loans
Keywords: Transportation, Automotive